Surveilans kesehatan dan edukasi gizi sebagai upaya deteksi dini dan pengendalian penyakit tidak menular di Desa Burai - Feranita Utama; Ningsih, Windi Indah Fajar; Lionita, Widya; Kurniati, Ardesy Melizah (Fakultas Kedokteran Universitas Sriwijaya, 2023)
The prevalence of non-communicable diseases tends to increase from time to time. Surveillance is one of efforts to control non-communicable diseases (NCDs). This service activity aims to increase knowledge and understanding of cadres regarding the importance of implementing community-based surveillance, measure risk factors for NCDs in the elderly, and increase community knowledge and understanding regarding efforts to prevent NCDs. The main activities in this service are strengthening cadres regarding NCDs surveillance, measuring risk factors, and nutrition education. The cadre strengthening activities were attended by 4 elderly posyandu cadres, 30 pre-elderly and elderly people participated in the measurement of NCDs risk factors, and 30 pre-elderly and elderly nutrition education participants. The results of NCDs risk factor measurement show that the majority of risk factor proportions are in the red category (alert) such as hypertension (80%), hyperglycemia (20%), obesity (60%), and high cholesterol (53.3%). Evaluation of nutrition education activities showed that there were significant differences in the average knowledge before and after the educational activities, with an increase in the average knowledge score after education of 2.292. The community is basically very enthusiastic about all the activities that have been held. NCDs risk factor data that has been collected in this activity can be used by policy makers as a basis for making decisions and needs support from the health office, puskesmas, village midwife, and village officials in activating posbindu activities in Burai Village such as measuring NCDs risk factors on a regular basis (recommended at least once every 6 months) in order to monitor and control NCDs risk factors and conduct NCDs education.